The effect of addition of silane coupling agent on the flexural strength of e-glass fiber non dental reinforced composite - Utami, Aisya Putri; Darmawangsa, Darmawangsa; Sari, Wwidya Puspita (Padjadjaran Journal of Dental Researchers and Students, 2024)
ABSTRACTIntroduction: One of the materials used in fixed denture treatment in clinical practice is porcelain fused to metal (PFM) but it has limitations such as poor aesthetics, metal materials that cause hypersensitivity in certain patients and fairly extensive abutment preparation. Alternative materials that can be used for fixed dentures are fiber reinforced composite (FRC) with E-glass fiber dental which has advantages such as bicom patibility, good aesthetics, and easy to adapt to the oral environment. Flexural strength is one of the mechanical properties in dental materials to withstand occlusal pressure. This flexural strength test is a description of the composite receiving loads during chewing activities. The availability of E-glass fiber dental in Indonesia is still limited with a fairly expensive price. Non-dental E-glass fiber has generally been used in the engineering field which has a composition almost the same as E-glass fiber dental. The purpose of this study was to determine the effect of adding silane coupling agent on the flexural strength of E-glass fiber non-dental reinforced composite. Methods: The research method used was an experimental method. Data analysis used the One Way Anova test. The test results on FRC with fiber given 2 times silane have the highest flexural strength with a value of 215.63 MPa. Results: Fiber without silane has the lowest value with a value of 168.12 MPa. Conclusion: The conclusion of this study is that there is an effect of adding silane coupling agent on the flexural strength of E-glass fiber non-dental Reinforced composite and is expected to be an alternative to replace E-glass fiber dental with good quality and affordable price.Keywords: E-glass fiber, Fiber reinforced composite, Silane coupling agent, Flexural StrengthPengaruh penambahan silane coupling agent terhadap kekuatan fleksural  e-glass fiber non dental reinforced compositeABSTRAKPendahuluan: Salah satu bahan yang digunakan pada perawatan gigi tiruan cekat dalam praktik klinis adalah porcelain fused to metal (PFM) namun memiliki keterbatasan seperti estetikanya yang kurang, bahan metal yang menyebabkan hipersensitifitas pada pasien tertentu serta preparasi abutment yang cukup luas. Alternatif bahan yang dapat digunakan untuk gigi tiruan cekat adalah fiber reinforced composite (FRC) dengan E-glass fiber dental yang memiliki kelebihan seperti bikompatibilitas, estetik yang baik, serta mudah beradaptasi di lingkungan mulut. Kekuatan fleksural merupakan salah satu sifat mekanis dalam material kedokteran gigi agar tahan terhadap tekanan oklusal. Pengujian kekuatan fleksural ini sebagai gambaran komposit menerima beban pada saat aktivitas pengunyahan. Ketersediaan E-glass fiber dental di Indonesia masih terbatas dengan harga yang cukup mahal. E-glass fiber non dental secara umum telah digunakan dibidang teknik yang memiliki komposisi hampir sama dengan E-glass fiber dental. Tujuan dari penelitian ini untuk mengetahui pengaruh penambahan silane coupling agent terhadap kekuatan fleksural E-glass fiber non dental reinforced composite. Metode: Metode penelitian yang digunakan adalah metode eksperimental. Analisis data menggunakan uji One Way Anova. Hasil uji pada FRC dengan fiber yang di beri 2 kali silane memiliki kekuatan fleksural tertinggi dengan nilai 215,63 MPa. Hasil: Fiber tanpa silane memiliki nilai terendah dengan nilai 168,12 MPa. Simpulan: Kesimpulan dari penelitian ini adalah bahwa terdapat pengaruh penambahan silane coupling agent terhadap kekuatan fleksural E-glass fiber non dental Reinfoced composite dan diharapkan dapat menjadi alternatif pengganti E-glass fiber dental dengan kualitas yang baik dan harga yang terjangkau.Kata Kunci: E-glass fiber, Fiber reinforced composite, Silane coupling agent, Kekuatan Fleksural